Convergence and stability of line search methods for unconstrained optimization. - Leong, Wah June; Goh, Bean San (Springer Verlag, 2013)
This paper explores the stability of general line search methods in the sense of Lyapunov, for minimizing a smooth nonlinear function. In particular we give sufficient conditions for a line search method to be globally asymptotical stable. Our analysis suggests that the proposed sufficient conditions for asymptotical stability is equivalent to the Zoutendijk-type conditions in conventional global convergence analysis.